Riset Pengaruh Pencapaian Akademik Terhadap Tingkat Stres Mahasiswa Menggunakan Metode Regresi Linier Berganda - Adi Saputra (Jurnal Riset Informatika dan Teknologi Informasi, 2025)
Stress is a condition that is felt when someone faces a challenge, or is in a situation that requires us to adjust quickly to a change. In the academic world, it is not uncommon for a student or student to experience stress due to several pressures such as assignments, exams, reports, and in the expected academic achievement. This study aims to analyze the effect of academic achievement on student stress levels, by applying multiple linear regression data mining methods. The data is obtained from 2028 students from 15 top-ranked universities in Bangladesh, including 9 public/government universities and 6 private universities. Through multiple linear regression analysis, this study evaluated the relationship between the independent variables, i.e., age of the students, GPA (Grade Point Average) of the students, frequency of feeling upset due to academic affairs, frequency of feeling unable to control important matters in academic affairs, frequency of feeling nervous and stressed due to academic pressure, frequency of feeling unable to cope with all mandatory academic activities, frequency of feeling confident in handling academic problems, frequency of feeling that academic affairs are going as desired, frequency of ability to control irritation in academic affairs, and the dependent variable, i.e., stress scores experienced by the students. This research provides insights for educational institutions to design strategies to help students manage academic stress, such as counseling and time management programs. By understanding the factors that influence stress, it is hoped that students can improve their psychological well-being during the lecture period.